Untangling regional development traps through narratives - Max Roessler (Regional Studies, Regional Science)
Based on two case studies in Germany, this study disentangles development traps by focusing on the role of narratives and imaginaries in peripheral regions. Drawing on 43 interviews and two focus groups, it shows how regions move towards development traps despite putative new opportunities through green transitions. The study highlights different narrative dimensions and how they serve as indicators for regional development trajectories. It expands the understanding of development traps and peripheral regions by showing how stories and imaginaries held by key actors materialise and become regional realities and calls for more place sensitivity.